2013
DOI: 10.1016/j.imlet.2013.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the polymorphisms in IFITM1 gene and their association in a Korean population with ulcerative colitis

Abstract: Interferon inducible transmembrane protein (IFITM) family genes have been implicated in several cellular processes such as the homotypic cell adhesion functions of IFNs and cellular anti-proliferative activities. We previously showed that the IFITM3 single nucleotide polymorphisms (SNPs) associated with susceptibility to ulcerative colitis (UC). The present study aimed to investigate whether the polymorphisms in the IFITM1 gene are associated with susceptibility to UC. We also evaluated the expression levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Recent studies have identified new roles for the IFITM family in Th differentiation and atopic and inflammatory disease, which are independent of their functions in cellular resistance to viral infection. 13,36,[80][81][82] Mouse studies showed that while IFITM deficiency was protective against induction of Th2 immune pathology and asthma, 13 it exacerbated Th17-driven inflammation in colitis, 82 highlighting the context dependency of their impact on inflammation. Clearly, further studies will be required to investigate the contribution of the different family members to the immune response and inflammation, and the cellular and molecular mechanisms that underlie their functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified new roles for the IFITM family in Th differentiation and atopic and inflammatory disease, which are independent of their functions in cellular resistance to viral infection. 13,36,[80][81][82] Mouse studies showed that while IFITM deficiency was protective against induction of Th2 immune pathology and asthma, 13 it exacerbated Th17-driven inflammation in colitis, 82 highlighting the context dependency of their impact on inflammation. Clearly, further studies will be required to investigate the contribution of the different family members to the immune response and inflammation, and the cellular and molecular mechanisms that underlie their functions.…”
Section: Discussionmentioning
confidence: 99%
“…78 Likewise, their expression is up-regulated in inflamed mucosa of ulcerative colitis and Crohn's disease patients, 43,79 and polymorphisms in IFITM1 and IFITM3 are associated with increased susceptibility to ulcerative colitis. 80,81 In mice, the IFITM family protect against colitis. 82 IFITM3 deficiency led to exacerbation of chemical-induced colitis, with increased infiltration of macrophages and effector T cells to the colon lamina propria, and biased CD4 + Th differentiation to Th17.…”
Section: The Ifitm Family In Allergic and Inflammatory Diseasementioning
confidence: 99%
“…In addition, due to their altered expression in transformed tissues, IFITM genes are overexpressed in colitis‐associated colon cancer and in severely inflamed mucosa of UC and CD patients . Furthermore, polymorphism in the IFITM3 and IFITM1 genes was found to be associated with susceptibility to UC …”
Section: Introductionmentioning
confidence: 99%
“…The NOD2 gene, which has been widely shown to influence both the susceptibility and phenotype of patients with CD, is located at the IBD1 locus [3,8,18]. We previously reported that an exon 4 variation of the Tim-1 gene and the SNPs of the IL27, TNFRSF17 and EED genes were associated with UC in a Korean population [5,6,9,19].…”
Section: Discussionmentioning
confidence: 99%